UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENGGAMBAR DI TK WHERDI KUMARA UNGGAHAN - Putu Eka Sastrika Ayu, Putu Yulia Angga Dewi, Kadek Ari Wisudayanti (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Motor development is one of the very important factors in the development of the child as a whole. Physical development is closely related to the child's motor development. Motor development includes rough and smooth motors. The Rough motor is a body movement that uses most of the muscles or the entire limbs affected by the maturity of the child itself. While the smooth motor is a movement that uses fine muscles or certain parts of the body, which is influenced by the opportunity to learn and practice. TK Wherdi Kumara Desa Unggahan, as one of the formal educational institutions that educate early childhood, experienced several problems related to teaching and learning activities. In this school, there are still some children with low fine motor skills. The low ability of the child's fine motor is seen from the number of children who have not been able to write properly. Looking at the problem, it is necessary to find the right solution to develop the smooth motor skills of the child. Many ways can be done to improve the child's fine motor, including withdrawing activities.